2017
DOI: 10.3126/ijasbt.v5i2.17317
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Perceptions and Practices of the Nurses to Prevent Indwelling Catheter Associated Infection; Jinnah Hospital Lahore, Pakistan

Abstract: Nursing is an art science and an essential health care profession in which the skilled knowledgeable persons are committed to provide care to sick peoples and strive for the, protection and promotion of health and prevention against diseases and helps to minimize the risk and risk related injuries. Urinary tract infections are very common infection in the hospital settings almost responsible for 40% nosocomial infections. All the urinray tract infection is expected that approximately more than 70% infection re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
3
2
1
Order By: Relevance
“…The odds of good practice towards catheter associated UTI prevention among nurses with > 10 years work experience was 5.44 times that of nurses with < 5 years of work experience [AOR = 5.44, 95% CI (1.66, 17.84)], Moreover the odds of good practice towards catheter associated UTI prevention among nurses with 5 to 10 years work experience was 3.59 times that of nurses with < 5 years of work experience [AOR = 3.59, 95% CI (1.46, 8.87)]. Similar finding was reported in studies conducted in India [ 40 ], Pakistan [ 20 ]. The finding might be justified as nurses’ experience increased; they become familiar with the subject matter thereby acquire good practice to carry out the procedure with safety and precision.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The odds of good practice towards catheter associated UTI prevention among nurses with > 10 years work experience was 5.44 times that of nurses with < 5 years of work experience [AOR = 5.44, 95% CI (1.66, 17.84)], Moreover the odds of good practice towards catheter associated UTI prevention among nurses with 5 to 10 years work experience was 3.59 times that of nurses with < 5 years of work experience [AOR = 3.59, 95% CI (1.46, 8.87)]. Similar finding was reported in studies conducted in India [ 40 ], Pakistan [ 20 ]. The finding might be justified as nurses’ experience increased; they become familiar with the subject matter thereby acquire good practice to carry out the procedure with safety and precision.…”
Section: Discussionsupporting
confidence: 79%
“…Even though 17–69% of catheter-associated urinary tract infections can be prevented by applying infection prevention methods, the knowledge and practice level of many nurses are not well known regarding catheter insertion, maintenance and removal [ 19 ]. According to the study conducted in Pakistan the adequate knowledge and practice level of nurses towards CAUTI prevention was 3.13% and 49% respectively [ 20 ]. Another study in Saudi Arabia shows that only 0.73% of nurses have adequate knowledge and 55.7% of nurses have good practice regarding CAUTI prevention [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nurses who had guidelines were 2.6 times more likely to have good knowledge regarding preventing CAUTIs than nurses who did not. This nding is consistent with a study conducted in Pakistan (45). This may be justi ed by the fact that the presence of guidelines will enhance the knowledge of nurses regarding CAUTI prevention (33).…”
Section: Discussionsupporting
confidence: 90%
“…The current study revealed that more than half (52.2%) of the study participants had good practice towards prevention of Catheter-associated UTIs. This finding is higher than the studies conducted in Pakistan [26], Philippines [16] and Egypt [17]. This discrepancy might be due to the educational status of the study participants, the difference in the study setting and the sample size.…”
Section: Discussioncontrasting
confidence: 65%